(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
The notion of \((ε,δ)\)-characteristic fuzzy sets is introduced. Given an ideal \(F\) of a \(BCK/BCI\)-algebra \(X\), conditions for the \((ε,δ)\)-characteristic fuzzy set in \(X\) to be an \((, \! q)\)-fuzzy ideal, an \((, q)\)-fuzzy ideal, an \((, \! q)\)-fuzzy ideal, a \((q,q)\)-fuzzy ideal, a \((q, )\)-fuzzy ideal, a \((q, \! q)\)-fuzzy ideal and a \((q, \! q)\)-fuzzy ideal are provided. Using the notions of \((α, β)\)-fuzzy ideal \(μ_F^(ε,δ)\), conditions for the \(F\) to be an ideal of \(X\) are investigated where \((α, β)\) is one of \((, \! q)\), \((, \! q)\), \((,q)\), \((q,\! q)\), \((q,\! q)\), \((q, )\) and \((q, q)\).